HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN BOUNDING ATTACHMENT DI RUANG NIFAS RSUD (RUMAH SAKIT UMUM DAERAH) dr. M. HAULUSSY AMBON - nanlohi, wildia; Manusama, Hansina; Wakano, Melawati; Makatita, Bazrul (STIKES Pasapua Ambon, 2023)
Introduction : Bounding attachment plays an important role in providing comfort and warmth to the baby, where the baby will feel loved, cared for, trusted and can foster social attitudes, so that the baby can feel safe and dare to explore. There are various ways to bond attachment, including Early Breastfeeding Initiation (IMD) and exclusive breastfeeding. Early initiation of breastfeeding can prevent bleeding after delivery and can reduce the infant mortality rate (IMR) in newborns due to hypothermia.Objective: To find out whether there is a relationship between the knowledge and attitudes of postpartum mothers and Bounding Attachment in the Postpartum Room at RSUD (Regional General Hospital) dr. M. Haulussy Ambon. Method: The design used in this research is quantitative analytical descriptive research with a cross sectional study approach. This research will be carried out in the Postpartum Room at RSUD (Regional General Hospital) dr. M. Haulussy Ambon. The sample in this study was all postpartum mothers, totaling 40 respondents, with the sampling technique being total sampling.Results: From the results of the analysis, the significance value between the relationship between knowledge and Bouding Attachment is (p= 0.000), which means there is a significant relationship between knowledge and Bouding Attachment, the significance value between the relationship between attitude and Bouding Attachment is (p= 0.000), which means there is significant relationship between attitude and Bouding Attachment. Conclusion: There is a significant relationship between knowledge and Bouding Attachment and there is a significant relationship between attitude and Bouding Attachment in the Postpartum Room at RSUD (Regional General Hospital) dr. M. Haulussy Ambon.